Early diagnosis of Lewy body disease in patients with late‐onset psychiatric disorders using clinical history of rapid eye movement sleep behavior disorder and [123I]‐metaiodobenzylguanidine cardiac scintigraphy. Issue 6 (10th April 2018) - Fujishiro, Hiroshige; Okuda, Masato; Iwamoto, Kunihiro; Miyata, Seiko; Torii, Youta; Iritani, Shuji; Ozaki, Norio
Abstract : Aim: Rapid eye movement sleep behavior disorder (RBD) and psychiatric symptoms often antedate the clinical diagnosis of Parkinson's disease or dementia with Lewy bodies. The purpose of this study was to investigate RBD and its relevance to Lewy body disease (LBD) in patients with late‐onset psychiatric disorders. Methods: Study subjects included 19 patients with late‐onset psychiatric disorders who exhibited REM sleep without atonia (RWA), which is a hallmark of RBD on polysomnography, at our psychiatric ward. Clinical profiles and radiological findings by cardiac [ 123 I]‐metaiodobenzylguanidine ([ 123 I]‐MIBG) scintigraphy and imaging for the dopamine transporter (DAT) were compared between patients with and without RBD symptoms. The correlations between the percentage of RWA in the total rapid eye movement sleep (%RWA) and radiological findings were also investigated. Results: Nine patients reported RBD symptoms only on specific questioning, but clinical profiles, including the prevalence of antipsychotropic usage, did not differ when compared to the remaining 10 patients without RBD (incidental RWA group). The median %RWA was significantly higher in the definite RBD group than in the incidental RWA group. Although the cardiac [ 123 I]‐MIBG uptake was significantly lower in the definite RBD group than in the incidental RWA group, there was overlap in the specific binding ratio on DAT scan. Conclusion: The severity of %RWA was highly correlated with the value of cardiac [ 123 I]‐MIBG uptake, but not with specific binding ratio on DAT scan. Clinical history of RBD and cardiac [ 123 I]‐MIBG scintigraphy are helpful for an early differential diagnosis of LBD from late‐onset psychiatric disorders, even before parkinsonism or dementia appears.